IMPLEMENTASI TUGAS SATUAN POLISI PAMONG PRAJA (SATPOL PP) DI BIDANG PENERTIBAN PEDAGANG KAKI LIMA (PKL) DI KABUPATEN BURU SELATAN IBUKOTA NAMROLE - GAY, ASNAWI (Patria Artha Management Journal, 2021)
This study aims to determine the implementation of the tasks of the Civil Service Police Unit  in the Control of Street Vendors, knowing the supporting factors, and knowing the factors that hinder the task of the Civil Service Police Unit in the field. Control of street vendors  in Buru Selatan district, the capital city of Namrole.This research is descriptive using a qualitative approach so that to support this research activity, data collection from informants is carried out. Data analysis is preceded by collecting and collecting data or information in the field, after which it is classifiedaccording to the type and group, then the analysis is carried out or interpreted qualitatively. Based on the results of the analysis, it is known that the implementation of the tasks of the Civil Service Police Unit in the Control of Street Vendors  in Buru Selatan Regency, thecapital of Namrole, has not been optimal so that many street vendors are still around. The factors that can support and hinder the task of the Civil Service Police Unit  in the Control of Street Vendors in Buru Selatan Regency, the capital of Namrole, are planned programs, related regulations, budgets, facilities and legal awareness of street vendors.